Pengaruh Viral Marketing dan Brand Awarness Terhadap Purchase Decision - Vina Islami; Heirunissa (Journal of Trends Economics and Accounting Research, 2025)
This study aims to examine the influence of viral marketing and brand awareness on consumer purchase decisions in Indonesia’s e-commerce sector. The research employed an associative quantitative method with a survey approach, distributing closed-ended questionnaires using a Likert scale to 180 respondents. Data were analyzed using the Structural Equation Modeling (SEM) technique based on SmartPLS. The findings indicate that viral marketing has a positive and significant effect on purchase decisions, demonstrating that promotional content disseminated massively through social media is effective in attracting consumer buying interest. Furthermore, brand awareness was also found to have a significant impact on purchase decisions, where a high level of brand awareness strengthens consumers’ tendency to choose a product. The study also reveals that viral marketing indirectly influences purchase decisions through increased brand awareness, which strengthens the brand’s position in consumers’ minds. The significance value for the effect of viral marketing on purchase decisions obtained a p-value of 0.000 < 0.05, indicating a positive and significant relationship. The significance value for the effect of brand awareness on purchase decisions was also p-value 0.000 < 0.05, confirming that brand awareness is essential for involving multiple brands in consumers’ consideration set during the purchase decision process. The significance value for the effect of viral marketing on brand awareness was p-value 0.000 < 0.05. These findings highlight the importance of integrating viral marketing strategies with brand awareness enhancement efforts to improve competitiveness in the e-commerce industry.